Musu' Selleng: Deconstruction of the Text and Context of Islamization in South Sulawesi, Indonesia - Amir, Muhammad; Aziz, Muhammad Nur Ichsan; Rismawidiawati,; Abu Muslim,; Ilyas, Husnul Fahimah; Hadrawi, Muhlis (Journal of Al-Tamaddun, 2024)
This article discusses the Musu’ Selleng in the process of Islamization in South Sulawesi in the 17th century. The data is presented using the historical method with a deconstruction approach to the text of historical events in the past. Islamization in South Sulawesi is often associated with political practices and community activities during the maritime trade network that strengthened the position of Islam as the religion of society in the past. This paper reveals that the Islamization process in South Sulawesi has unique dynamics based on text analysis and the context of events that influence the Islamization process has two important meanings in Indonesia, namely as a socio-religious role and a political role that strengthens the structure and order of a community. The expansion of Islam in South Sulawesi was influenced by the three major Islamic powers, namely Gowa-Tallo, Bone, and Wajo, which positively impacted the development of Islam in South Sulawesi. The main objective of this article is to try to deconstruct the historical events of Islam in South Sulawesi based on the texts and contexts that influenced their development. The integration of the Islamization process in South Sulawesi will strengthen the view of the current currents of Islamization that are developing in Indonesia.